2009
DOI: 10.1016/j.neuroscience.2009.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and space: lateralized emotional word detection depends on line bisection bias

Abstract: Emotion and space: lateralized emotional word detection depends on line bisection bias Tamagni, C; Mantei, T; Brugger, P There is converging evidence, from various independent areas of neuroscience, for a functional specialization of the left and right cerebral hemispheres for positive and negative emotions, respectively ("valence theory" of emotional processing). One subfield, however, has produced mixed results, i.e. work on the detection of parafoveally presented positively or negatively emotional words by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Evidence for such affect-triggered implicit knowledge has been reported in the clinical literature (Marshall & Halligan, 1988), and emotional cues can also shift the perceived midpoints of lines for healthy individuals (Mohr & Leonards, 2007). The quantitative method introduced here may encourage a more in-depth exploration of the interactions between emotions and space more generally (Tamagni, Mantei, & Brugger, 2009). In addition, recognition of reference point biases may enrich knowledge about both the behavioral neurology of the neglect syndrome and the processes underlying spatial location estimates.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence for such affect-triggered implicit knowledge has been reported in the clinical literature (Marshall & Halligan, 1988), and emotional cues can also shift the perceived midpoints of lines for healthy individuals (Mohr & Leonards, 2007). The quantitative method introduced here may encourage a more in-depth exploration of the interactions between emotions and space more generally (Tamagni, Mantei, & Brugger, 2009). In addition, recognition of reference point biases may enrich knowledge about both the behavioral neurology of the neglect syndrome and the processes underlying spatial location estimates.…”
Section: Discussionmentioning
confidence: 77%
“…Because line bisection and emotion processing both involve the right temporoparietal region, some have suggested that these activities may be related (e.g., Drago et al, 2008;Foster et al, 2008). Support for this idea has been found when line bisection performance was treated as a trait-like indicator of general spatial-attentional ability Tamagni, Mantei, & Brugger, 2009). Relevant to the present study, Drago et al grouped participants based on line bisection accuracy in order to examine how visuospatial attention related to emotion processing.…”
Section: Relationship Between Line Bisection Performance and Emotion mentioning
confidence: 66%
“…Four studies investigated whether the presentation of emotional words with positive and negative valence modulated the performance on the perceptual line bisection and landmark task. Of these, one study reported that emotional words enhance the rightward bias [31], one reported that negative words attenuate the rightward bias [32], one study reported that emotional words enhance the leftward bias [29], and one reported a positive relationship between the detection of negative words and leftward bias [33].…”
Section: Wordsmentioning
confidence: 99%